Macroeconomic determinants of the issuance of initial public offering (IPO) among three Asean countries / Nur Fahmida Zainal Abidin - Zainal Abidin, Nur Fahmida (2019)
The changes in macroeconomic variables might affect the stock market. This research seeks to address the question of whether local macroeconomic variables have any influence on the numbers of Initial Public Offerings (IPOs) in an emerging market within three (3) ASEAN countries which are Malaysia, Singapore and Thailand over the period of 2001-2017. There is evidence of a significant negative relationship between interest rate (IR) and the number of IPOs. On the other hand, there is insignificant negative relationship between Inflation rate (INF) and the number of IPOs are found. Besides, there are insignificant positive relationship between Growth Domestic Product (GDP) and Foreign Direct Investment (FDI) and the number of IPOs are found. Using panel data and multiple linear regressions, the result show strong significant relationships of IR to the number of IPOs. On the other hand, investors and companies believe the role of government to control the macroeconomic variables will give them confidence to go to public. Researcher hopes that this research will guide them on the suitable timing and economic condition for going public in reference to historical trends of issuance.